2021
DOI: 10.1021/acs.jnatprod.1c00002
|View full text |Cite
|
Sign up to set email alerts
|

Agaricus bisporus-Derived Glucosamine Hydrochloride Facilitates Skeletal Injury Repair through Bmp Signaling in Zebrafish Osteoporosis Model

Abstract: Glucosamine hydrochloride (GAH), one of the most basic and important derivatives of chitin, is obtained by hydrolysis of chitin in concentrated hydrochloric acid. At present, little is known about how GAH functions in skeletal development. In this report, we demonstrate that GAH, extracted from the cell wall of Agaricus bisporus, acts in a dose-dependent manner to promote not only cartilage and bone development in larvae but also caudal fin regeneration in adult fish. Furthermore, GAH treatment causes a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…However, the transcriptional level of mmp9 was clearly decreased as compared to dexamethasone‐treated zebrafish (Figure 8C). Moreover, we also detected the mRNA levels of bmp2b and bmp4 , two members of bone morphogenetic proteins that induce the formation of bone and cartilage [30, 33] . Results showed that the expression levels of bmp2b and bmp4 were both significantly enhanced in a roughly dose‐dependent manner after treatment of 7 (Figure 8C).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…However, the transcriptional level of mmp9 was clearly decreased as compared to dexamethasone‐treated zebrafish (Figure 8C). Moreover, we also detected the mRNA levels of bmp2b and bmp4 , two members of bone morphogenetic proteins that induce the formation of bone and cartilage [30, 33] . Results showed that the expression levels of bmp2b and bmp4 were both significantly enhanced in a roughly dose‐dependent manner after treatment of 7 (Figure 8C).…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, we also detected the mRNA levels of bmp2b and bmp4, two members of bone morphogenetic proteins that induce the formation of bone and cartilage. [30,33] Results showed that the expression levels of bmp2b and bmp4 were both significantly enhanced in a roughly dose-dependent manner after treatment of 7 (Figure 8C). The data showed that tricrilactones may ameliorate osteoporosis by remolding the balance between bone formation and bone resorption, and simultaneously promoting cartilage and skeletal development.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…As osteoporosis is characterized by an imbalance between bone resorption and bone formation, current drugs for osteoporosis either inhibit bone resorption, or stimulate bone formation. [30] Alkaline phosphatase (ALP) and tartrate resistant acid phosphatase (TRAP) are biomarkers during osteoporosis, with the former reflecting osteoblast differentiation (bone formation), and the latter embodying the activity of osteoclast (bone resorption). [31] To learn the mechanism for the antiosteoporosis action of tricrilactones on zebrafish, we assessed the quantities of these two markers.…”
Section: Methodsmentioning
confidence: 99%